2024
DOI: 10.3390/antibiotics13010078
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antiviral Properties of Chenopodin-Derived Synthetic Peptides

Marcia L. Feijoo-Coronel,
Bruno Mendes,
David Ramírez
et al.

Abstract: Antimicrobial peptides have been developed based on plant-derived molecular scaffolds for the treatment of infectious diseases. Chenopodin is an abundant seed storage protein in quinoa, an Andean plant with high nutritional and therapeutic properties. Here, we used computer- and physicochemical-based strategies and designed four peptides derived from the primary structure of Chenopodin. Two peptides reproduce natural fragments of 14 amino acids from Chenopodin, named Chen1 and Chen2, and two engineered peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Especially, a group of peptides with antimicrobial activity, including human endogenous β-defensins (hBDs) 1-3, cathelicidin antimicrobial peptide (LL-37), and dermcidins, is known to have a beneficial role in wound-healing processes [28,29]. Recent studies have shown that computational methods can also predict other peptides or proteins with antimicrobial properties that are significantly involved in wound-healing applications [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, a group of peptides with antimicrobial activity, including human endogenous β-defensins (hBDs) 1-3, cathelicidin antimicrobial peptide (LL-37), and dermcidins, is known to have a beneficial role in wound-healing processes [28,29]. Recent studies have shown that computational methods can also predict other peptides or proteins with antimicrobial properties that are significantly involved in wound-healing applications [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…These short peptide sequences may exhibit better characteristics in terms of charge, structure, and overall antimicrobial effect compared to whole antimicrobial proteins [ 19 ]. In turn, some peptides designed in silico, modified, and synthesized may demonstrate antimicrobial effects comparable to or even better than those of natural counterparts [ 20 ]. Designing new synthetic peptides can be used not only to enhance their antimicrobial effects but also for broader applications in various fields [ 21 ].…”
Section: Introductionmentioning
confidence: 99%